Conjecture on Minimum Covariance Determinant (MCD) Location and Scatter - A. Djauhari, Maman (Institute for Mathematical Research, 2009)
We review Rousseeuw and van Driessen's basic theorem of Fast MCD algorithm. Later on, we present a conjecture that if minimum covariance determinant in Fast Men is replaced by minimum vector variance (MVV), then the results are not changed. The importance of this conjecture lies in the computational efficiency of the algorithm where a multilinear form is replaced by a quadratic form.